Active Transportation of Liposome Enhances Tumor Accumulation, Penetration, and Therapeutic Efficacy. Issue 44 (8th October 2020) - Wang, Guowei; Wu, Bihan; Li, Qunying; Chen, Siqin; Jin, Xiaoqin; Liu, Yajing; Zhou, Zhuxian; Shen, Youqing; Huang, Pintong
Abstract: Liposomes are the first and mostly explored nanocarriers for cancer drug delivery, which have shown great promise in clinical applications, but their limited accumulation and penetration into the tumor interstitial space, significantly reduce the therapeutic efficacy. Here, a γ‐glutamyltranspeptidase (GGT)‐triggered charge‐switchable approach is reported that can trigger the fast endocytosis and transcytosis of the liposome in tumor microenvironments to overcome the harsh biological barriers in tumor tissues. The active transporting liposomal nanocarrier (GCSDL) is prepared by surface modification with a glutathione (GSH) moiety and encapsulated with doxorubicin (DOX). When the GCSDL contacts with tumor vascular endothelial cells, the overexpressed GGT enzyme on cytomembrane catalyzes the hydrolysis of GSH to generate cationic primary amines. The cationic GCSDL triggers fast caveolae‐mediated endocytosis and vesicle‐mediated transcytosis, resulting in sequential transcytosis to augment its tumor accumulation and penetration. Along with continual intercellular transportation, GCSDL can release DOX throughout the tumor to induce cancer cell apoptosis, resulting in complete eradication of hepatocellular carcinoma and cessation of pancreatic ductal adenocarcinoma's progression. This study develops an efficient strategy to realize high tumor accumulation and deep penetration for the liposomal drug delivery system via active transcytosis. Abstract : An active transporting liposomal nanocarrier (GCSDL) is developed by surface modification of liposome with a glutathione moiety and encapsulation with doxorubicin. The GCSDL undergoes γ‐glutamyltranspeptidase‐triggered cationization in tumor microenvironments, initializes efficient transcytosis by endothelial cells and cancer cells, transports actively into deep tumors, and releases doxorubicin throughout tumor to induce cancer cell apoptosis.